Предмет: Алгебра,
автор: Аноним
296(1,2) Упростите выражение с квадратными корнями , подробное решение .
Приложения:
Ответы
Автор ответа:
2
1) (√а(√а-√в)+ √в(√а+√в))/(√а+√в)(√а-√в) + 2√ав/(а-в) *(√a-√b) = (а-√ав+в+√ав)/(а-в) + 2√ав/(а-в) *(√a-√b) = √а^2+2√ab+√b^2/(√a+√b)(√a-√b) *(√a-√b) = (√a+√b)-(√a+√b)*(√a-√b)= (√a+√b)
Похожие вопросы
Предмет: Литература,
автор: smirnoff4ik2006
Предмет: Математика,
автор: aamangeldy2010
Предмет: Русский язык,
автор: romanajrih928
Предмет: Математика,
автор: fgbfhfhfdhfdFadewj
Предмет: Математика,
автор: noob10